Enhancing analgesic spinal cord stimulation for chronic pain with personalized immersive virtual reality. Issue 6 (June 2021) - Solcà, Marco; Krishna, Vibhor; Young, Nicole; Deogaonkar, Milind; Herbelin, Bruno; Orepic, Pavo; Mange, Robin; Rognini, Giulio; Serino, Andrea; Rezai, Ali; Blanke, Olaf
Abstract : Abstract: Spinal cord stimulation (SCS) is an approved treatment for truncal and limb neuropathic pain. However, pain relief is often suboptimal and SCS efficacy may reduce over time, requiring sometimes the addition of other pain therapies, stimulator revision, or even explantation. We designed and tested a new procedure by combining SCS with immersive virtual reality (VR) to enable analgesia in patients with chronic leg pain. We coupled SCS and VR by linking SCS-induced paresthesia with personalized visual bodily feedback that was provided by VR and matched to the spatiotemporal patterns of SCS-induced paresthesia. In this cross-sectional prospective interventional study, 15 patients with severe chronic pain and an SCS implant underwent congruent SCS-VR (personalized visual feedback of the perceived SCS-induced paresthesia displayed on the patient's virtual body) and 2 control conditions (incongruent SCS-VR and VR alone). We demonstrate the efficacy of neuromodulation-enhanced VR for the treatment of chronic pain by showing that congruent SCS-VR reduced pain ratings on average by 44%. Spinal cord stimulation–VR analgesia was stronger than that in both control conditions (enabling stronger analgesic effects than incongruent SCS-VR analgesia or VR alone) and kept increasing over successive stimulations, revealing the selectivity and consistency of the observed effects. We also show that analgesia persists after congruent SCS-VR had stopped, indicating carry over effects and underlining its therapeutic potential. Linking latest VR technology with recent insights from the neuroscience of body perception and SCS neuromodulation, our personalized new SCS-VR platform highlights the impact of immersive digiceutical therapies for chronic pain. Registration: clinicaltrials.gov, Identifier: NCT02970006. Abstract : This study describes a new digiceutical platform merging spinal cord stimulation with immersive virtual reality that enhances neuromodulation-induced analgesia in patients with chronic pain.